Structure and zonation of algal communities on the bay of São Vicente (São Miguel, Azores). - Neto, Ana I. (2013)
III Simpósio Fauna e Flora das Ilhas Atlânticas”. Ponta Delgada, Açores, 21-25 de Setembro de 1998.